2004
DOI: 10.1017/s1478951504040362
|View full text |Cite
|
Sign up to set email alerts
|

Hospice staff members' views on conducting end-of-life research

Abstract: Although many of the opinions derived from the survey appear to indicate a willingness to embrace research in a hospice setting, significant barriers, especially time constraints and protective attitudes, remain. Educational efforts and firsthand involvement in the research process might be a useful first step in attempting to address these barriers and traditionally held beliefs against using hospice patients and families in research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Most studies (14) based their findings on individuals’ directly reported experiences of participating themselves in a research study. The other studies approached the topic indirectly by enquiring about attitudes [15,16], by enquiring about participants’ settled opinions or ways of thinking about research; or asking hypothetical questions [17-20] to respondents where they are asked about a supposed situation where people who receive palliative care are invited to participate or are participating in research. These categories are denoted in Table 2 as D (direct), A (attitudinal), and H (hypothetical).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies (14) based their findings on individuals’ directly reported experiences of participating themselves in a research study. The other studies approached the topic indirectly by enquiring about attitudes [15,16], by enquiring about participants’ settled opinions or ways of thinking about research; or asking hypothetical questions [17-20] to respondents where they are asked about a supposed situation where people who receive palliative care are invited to participate or are participating in research. These categories are denoted in Table 2 as D (direct), A (attitudinal), and H (hypothetical).…”
Section: Resultsmentioning
confidence: 99%
“…Kirsch et al conducted a cross-sectional anonymous survey with hospice staff to gain insight into staff’s attitudes, beliefs and values about research with the patients they cared for and their families. They found that staff were largely supportive of research, but they acknowledged a mix of protectionism towards patients and not having enough time for research as barriers to participation [15]. Williams et al focused on hospice patients and carers and compared their interest in research with ambulatory senior citizens.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Certainly there is a positive attitude to research in the abstract—most participants in Kirsh’s16 study agreed strongly that they would be supportive about research involving patients or families, they were also clear that they were protective of patients and more practically that their clinical workload precluded them from active support or involvement. As Fine17 points out, the gatekeeping role by clinical staff may itself be immoral:…”
Section: Vulnerability Altruism and Gatekeepingmentioning
confidence: 99%